2006
DOI: 10.3727/000000006783981864
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Ossification in the Scar Tissue of Rats with Myocardial Infarction

Abstract: We describe the occurrence of bone-like formations in the left ventricular wall of infarcted rats treated or not with bone marrow cells injected systemically or locally into the myocardium. The incidence of ectopic calcification in hearts has been reported in rare cases in children with infarcts without previous coronary artery disease. Recently, ventricular calcification has been correlated with unselected bone marrow cell transplantation into infarcted rat hearts. Echocardiographic analysis of large infarcti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
0
6
1
Order By: Relevance
“…We here addressed these important questions by using (1) genetically labeled cells, (2) whole BM and different fractions of BM-derived cell populations, (3) careful characterization of the cell biologic properties of the MSCs and their in vitro differentiation potential, (4) different types of myocardial infarction models, (5) a large number of different control conditions, and (6) direct injection of cells as well as BM mobilization. Our present study in mice and the earlier in rats 24 could not identify, as reported recently for rat hearts, 23 a high incidence of calcifications after myocardial infarction independent of cell transplantation.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…We here addressed these important questions by using (1) genetically labeled cells, (2) whole BM and different fractions of BM-derived cell populations, (3) careful characterization of the cell biologic properties of the MSCs and their in vitro differentiation potential, (4) different types of myocardial infarction models, (5) a large number of different control conditions, and (6) direct injection of cells as well as BM mobilization. Our present study in mice and the earlier in rats 24 could not identify, as reported recently for rat hearts, 23 a high incidence of calcifications after myocardial infarction independent of cell transplantation.…”
Section: Discussioncontrasting
confidence: 80%
“…This excluded tissue-derived heterotopic calcifications as underlying cause that were found after acute myocardial infarction in a few human patients 21,22 and more frequently in rats. 23 Direct involvement of the transplanted cells in the generation of calcifications/ossifications rather than an unspecific tissue response was clearly supported by the observation that transplanted cells generated osteocalcin at an early stage, whereas at later stages the massive bone formation led to decellularized central areas. Calcifications after injection of BM cells into the infarcted rat myocardium were reported earlier.…”
Section: Discussionmentioning
confidence: 91%
“…Further, our data supports a recently published paper by Ribeiro et al . in 2006, in which they showed that chondro-osteogenic differentiation can take place in the Wistar rat heart independent of animal treatment with bone marrow cells 28.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ectopic calcification was perceived as the end stage of affected tissue and was not considered important (8,9). Although ectopic calcification is considered benign, it is often a cause of various other diseases and patient prognosis is much worse when calcification is present (10,11). Recently, studies have made significant progress on elucidating the biology of normal bone metabolism, which has facilitated research on ectopic calcification at the same time.…”
Section: Ectopic Calcificationmentioning
confidence: 99%